Ideological connection between Negara Islam Indonesia (NII) And Jama'ah Islamiyyah (JI): study on their deviation and approaches toward the Qur'an - Jani, Mohd. Shah (s.n, 2013)
The research attempts to reveal the emergence of hardliner Muslim group in Indonesia who from the inception got the ambition to establish an Islamic government with the application of the Shariah. The Islamic State of Indonesia known as Negara Islam Indonesia (NII) was proclaimed in 17 of August, 1949, in West Java by S.M. karosoewirjo. Since the day of independence he got frustrated to see failure of Muslim leadered Jihad against the central government and the struggle lasted for thirteen years until he was given the death penalty by the then Indonesian Court of justice. The research also aim at exposing the crystallization of the movement following his death the policy of New Order Government led by Suharto